Kant’s Enlightenment as a Critique of Culture - Piché, Claude (Con-Textos Kantianos. International Journal of Philosophy, 2015)
It is puzzling to notice that in his 1784 essay on Enlightenment, Kant addresses every human being with his watchword « Have the courage to use your own understanding! », while at the same time he seems to restrict the access to the public discussion of matters of common interest to the learned persons (Gelehrte). This begs the question: Is the participation in the public debate part and parcel of Kant’s conception of Aufklärung? A positive answer to this question is given by Katerina Deligiorgi in her Kant and the Culture of Enlightenment. A critical assessment of this book will lead us however to consider that Kant has a differentiated approach to enlightenment depending on whether someone is educated or uneducated. Following Rousseau, Kant has come to recognize as a matter of fact this inequality toward the products of culture. Now the two-level conception of enlightenment entailed by this inequality becomes explicit in the 1790s, especially in the very last work Kant has published: The Conflict of the Faculties (1798).